PROBLEM-SOLVING ABILITY IN REALISTIC MATHEMATICS EDUCATION BASED ON HYPOTHETICAL LEARNING TRAJECTORY - Maulida, Dini Wardani; Mahmudah, Mutiara Hisda; Hidayati, Miftachul; Setyaningsih, Nining; Sutarni, Sri (Universitas Bhinneka PGRI, 2025)
Problem-solving ability is one of the essential learning characteristics in 21st-century skills, which requires students to think critically during the problem-solving process. Thus, the purpose of this study was to describe students' problem-solving skills in HLT-based RME learning. This research used a qualitative method with a case study design. The research was implemented in SMP Negeri 3 Satu Atap Tawangharjo. The research subjects were the principal, math subject teacher, and seventh-grade students. Data validity used triangulation of methods and sources. Data analysis technique with flow method. The results showed that some students had high, medium, and low mathematical problem-solving abilities in solving math problems. In conclusion, students' problem-solving ability in HLT-based RME learning has a high percentage. The percentage of students with high problem-solving ability is 75%, those with moderate problem-solving ability make up 15%, and those with low problem-solving ability account for 10%. Thus, students who were able to solve problems in HLT-based RME learning were more than students who were not able to solve problems in HLT-based RME learning.